A simple elastic phononic crystal plate with adjustable topological valley transmission paths. (November 2022) - Ma, Ze; Liu, Yang; Xie, Yu-Xin; Wang, Yue-Sheng
Abstract: The study of topological insulator devices has now been extended from electromagnetic and acoustic waves to the field of elastic waves. Topology-protected wave transmission has stimulated great interest due to its strong robustness. In this paper, we design an elastic phononic crystal plate (EPCP) with tunable topological valley transmission. The inversion of the topological energy band is attained just by adjusting the relative height of the bolts. Moreover, by calculating the topological invariants, the topological property of this EPCP is further demonstrated. The topological boundary transport immunity to defect, sharp bend, and disturbance is verified using the finite element method and experiments. By simply regulating the relative heights of the bolts in the unit cell, topological valley transmission for different shaped paths is achieved, which is important for the practical application of tunable topology elastic wave transmission devices.